Application Of Income Tax Reporting Article 21 On Employees Salary In Unika Widya Mandala - Abadi, Andreas Johan Hendrixancaka; Soebijono, Tony; Nurcahyawati, Vivien (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2018)
Recording employee income tax at Widya Mandala Catholic University is an application that helps overcome the existing problems. The number of forms of income received by employees in the scope of Widya Mandala Catholic University of course also add income tax to be paid to the State. The amount that must be stored can not be less or more. If less then it will be regarded as a tax debt, but if there is more pay then what happens is there will be a detailed financial examination of the operational University of Widya Mandala.This application can perform the calculation of employee income tax more accurately so it is expected to help reporting income tax article 21 Unika Widya Mandala to be more accurate in accordance with the expenditure of income.With the application of income tax calculation of 21 employees, the management of Widya Mandala University can find out how much income tax should be reported in order to avoid things that are detrimental to university activity